ANALYSIS OF READING MATERIALS IN ENGLISH WAY 2 TEXTBOOK FOR JUNIOR HIGHSCHOOL - Fadhil, Muhammad Resky; Mardiana, Hj. (ETERNAL (English, Teaching, Learning, and Research Journal), 2017)
This research aimed to analyze Reading material in English textbook “English Way 2” for Junior highschool student. Reading is one of the most important skill in learning english, because with reading skill we can learn english from written materials such as textbook. Reading materials is source that used for teaching reading, the materials must be appropriate with level of student, not only the level of reading text, genre of the text and content of lexical density of the text must be appropriate to.The research method of this research was qualitative descriptive, for specific this research is library research or content analysis research. The data of this research collected form reading text in “English Way 2” textbook. There are 8 reading text collected from the book. Having analyzed the data of this research, this book contain 3 genres of the text such as descriptive, recount, and narrative. There are 2 descriptive text, 5 recount text, and 1 narrative text. The genre itself is appropriate with syllabus English Learning KTSP 2006 for 8th grade student junior high school. The level of lexical density of reading text in “English Way 2” textbook for grade 8th is around 40% - 50% lower lexical density, it means the text or reading materials from the book is easy to understand, and also the reading materials is suitable for student as a main or sub materials for reading.